Azadipyrromethenes for applications in photodynamic antimicrobial chemotherapy, photodynamic therapy and optical limiting - Dubazana, Nadine (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
Azadipyrromethenes, azaBODIPYs and zinc azadipyrromethene complexes were prepared and characterised to examine the effect on their photophysical properties of incorporating phenyl groups at the 1,3,5,7-positions with electron-donating and withdrawing groups at the para-positions. To enhance their ability to generate singlet oxygen, appropriate structural modifications were made through the addition of a Zn(II) ion or halogenation at the 2,6 positions. In vitro photodynamic therapy (PDT) studies targeting MCF-7 human breast cancer cells were carried out. To evaluate and understand the effectiveness of the dyes as photosensitisers, cellular uptake, phototoxicity and the half-maximal inhibitory concentration (IC50) values were analysed. Photodynamic antimicrobial chemotherapy (PACT) studies were also carried out to study the effectiveness of the dyes against Staphylococcus aureus (S. aureus). Dyes with donor-Ï€-acceptor (D-Ï€-A) properties were synthesised and tested against the second harmonic of the Nd:YAG laser in optical limiting (OL) studies. The second-order hyperpolarisability, third-order susceptibility and nonlinear absorption coefficient values were determined. The results suggest that 1,3,5,7-azaBODIPY dyes may be less suitable for use in this context than analogous D-Ï€-A 3,5-distyrylBODIPY dyes. Molecular modelling was carried out to identify the structure-property relationships of the synthesised dyes by analysing trends in the energies of the frontier molecular orbitals (MOs) and spectroscopic properties.
Keywords: Dyes and dyeing -- Chemistry; Photochemotherapy; Cancer -- Photochemotherapy; Anti-infective agents; Staphylococcus aureus; Nonlinear optics; Azadipyrromethenes; BODIPY